Problems With Assessing Student Autonomy in Higher Education, an Alternative Perspective and a Role For Mentoring - Andrew G Holmes (ÜNİVERSİTEPARK Limited, 2018)
The paper explores, from a conceptual basis, the inherent tensions in assessing student autonomy in higher education. The author argues that, despite the development of student autonomy being a key aim of higher education, there are problems in identifying with any level of precision what it is, and that its assessment is highly problematic. An alternative perspective is provided that, with the support of mentoring processes, allows for authentic assessment. The paper is intended to stimulate debate amongst university management and academic practitioners in higher education. This is a conceptual paper considering the problematic nature of learner autonomy and the inherent difficulties in assessing it, with a practical potential solution proposed.